Parents/Guardians’ Gender Preferences, Confidence, and Empathy for their Children’s Dentist - Gabrielle Carvalho; Ivana Meyer Prado; Larissa Kelen Moura; Yanna Cardoso-Santos; Talyta Couto Freitas; Raquel Fabiane Nogueira; Iga Carnevalli; Junia Maria Serra-Negra (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To analyze the factors that influence parents’/guardians’ gender preference, confidence level, and empathy level in the dentist treating their child, as well as the factors associated with parents’/guardians’ preference for the dentist's gender identification. Material and Methods: A total of 104 parents/guardians of patients from the pediatric dental clinic of a Brazilian University participated in this cross-sectional study. Data collection occurred in the clinical waiting room by applying a questionnaire about sociodemographic information, characteristics of the dentist that most caught parents’/guardians’ attention, whether the child’s dentist’s gender identification matters to parents’/guardians’, and analog scales designed by the research team gauging preferences in dentist's gender, confidence level and empathy level in their child’s dentist. Statistical analysis was performed using Mann-Whitney U and Kruskal-Wallis tests (p<0.05). Results: Most participants were female (74%) and mothers of patients (63.5%). The proportion of parents/guardians lacking confidence about their child's dentist was higher among those who considered the dentist’s gender identification significant (p=0.045). The empathy scores of parents/guardians toward their child's dentist were higher among female parents/guardians (p=0.012). Parents/guardians who reported caring about the dentist’s gender identification had lower preference scores for an LGBTQ+ dentist (p=0.018). Conclusion: There was no significant difference in the preference for female or male dentists. A low preference for LGBTQ+ dentists was observed among parents/guardians, demonstrating homophobic behavior.